Factors influencing the adsorption of antibiotics onto activated carbon in aqueous media. (18th October 2022) - Singh, Surya; Lundborg, Cecilia Stålsby; Diwan, Vishal
Abstract: Widespread use of antibiotics for treating human and animal ailments has increased their discharge in the environment through excreta. Moreover, unscientific disposal of unused antibiotics has further increased their presence in the environmental matrices. Thus, occurrence of used and/or discarded antibiotics in water resources is becoming a growing concern across the globe. Antibiotics and their residues in the aquatic environment are emerging contaminants which pose a serious threat to the aquatic biota as well as human beings by enhancing antibiotic resistance. Various methods are being adopted for the removal of these contaminants. Adsorption over activated carbon is one such promising method which is environmentally friendly, cost-effective, and efficient. However, there are various factors which affect the overall process efficiency, such as, properties of activated carbon/antibiotics/reaction medium etc. In this article, emphasis has been laid down on evaluating these factors, so that the experimental procedures may be optimized to obtain the highest possible removal efficiency for antibiotics in the aqueous media. HIGHLIGHTS: Antibiotic resistance is a growing concern. Adsorption processes play a significant role in the removal of antibiotics from aqueous media. Adsorption onto activated carbon is influenced by various process parameters. Optimization of process parameters is essential to obtain the highest possible removal efficiency. Graphical Abstract